Developing The Strength Of Youth Football Players During Pre-Competition Preparation (Texas Journal of Multidisciplinary Studies, 2025)
The article discusses the development of strength training in football players during precompetition preparation, the development of strength through repeated exercises, and the need to impose a certain requirement on football players: the ability to use physical qualities as a means of increasing game efficiency.